Properties of generalized synchronization of chaos - Pyragas, K. (Nonlinear Analysis: Modelling and Control, 1998)
A review of recent ideas in the field of generalized synchronization of chaos is presented. This field is concerned with a generalization of the concept of conventional (identical) chaotic synchronization to the case of one-way coupled nonidentical chaotic systems. Generalized synchronization is taken to occur if, ignoring transients, the response system becomes uniquely determined by the current state of the driving system, i. e., all trajectories in the phase space are attracted to a complex synchronization manifold that may have a fractal structure. Different tools for detecting and analyzing the properties of this type of synchronization are discussed.
Keywords: none